Sustainability Performance Approach in Malaysia’s SMEs for Improving Green Supply Chain Management (GSCM); An Application of Quality Function Deployment (QFD) - Mohd Rozar, Norlinda; Razik, Muhammad Ashlyzan; Zakaria, Mohd Nazri (International Journal of Supply Chain Management, 2019)
Many perceptions from environmental studies were claimed that environmental pollution in Malaysia is due to the failure of Green Supply Chain Management (GSCM) among Small Medium Enterprise (SMEs). There is a need to see an effective strategy to overcome the GSCM failures or to improve the GSCM in SMEs. Since, "green supply chain management (GSCM)" was introduced as a driver for sustainable performance in environmental preservations achievement throughout the supply chain. The objective of this study is to identify the key of performance for GSCM measurement in SMEs. Analysed the quantitative data by SPSS and the results show 2 factors affect the performance namely GSCM Benefits and Critical Success factor. Consumer safety contributed significantly in GSCM benefits while, high satisfaction of customers and business partners in SCs contributed significantly in critical success factor. Based on both factor of GSCM performance, this study developed a model for GSCM improvements by Quality Function Deployment (QFD) method development toward sustainability performance (Environment, Economy and Social) and operational factor has been found at the end of the result as a complementary for the improvements. In terms of the sustainability performance impact, the result of Quality Functions Deployment (QFD) found that social is the most important parameter for GSCM improvement in Malaysias manufacturing SMEs followed by the economy, operational, and environment. Finally, this study has concluded that emphasizing the social factor is much help for reduce the environmental pollution in Malaysia and achieves the sustainability performance in the industry as well.